(untitled) (Web of Teachers: Inderscience Research, 2026)
The article discusses advanced foreign methods of attracting investment in the field of tourism services. It is shown that the development of tourism infrastructure, improving the quality of service and the formation of a competitive destination directly depend on the effectiveness of investment policy. On the basis of scientific and educational literature, such mechanisms as public-private partnership, tax benefits, special tourist zones, cluster approach, digital promotion and territorial branding.